Is nutritional care a human right? (2019)
Background & aims The high prevalence of disease-related malnutrition is a major public health issue worldwide despite the fact that the efficacy of nutritional care has been extensively documented. Therefore, it is needed to move forward on stronger public health policies. The aim of our article is to analyze the link between nutritional care and human rights. We wonder whether it is possible to consider nutritional care as a human right. Methods We examine the relationship between nutritional care and human rights by using the human rights-based approach. It allows us to determine the grounding of the nutritional care as a human right, the duty-bearers and its content or scope. Results The difficulties in the conception and realization of the right to food in the clinical context and the possibility to define a specific scope for nutritional care within the care-giving context shows that the right to nutritional care can be considered as a human right by itself and closely related to the right to food and the right to health. The human right to nutritional care implies that the patient has the right to beneficiate from the right to be screened for malnutrition and receive a malnutrition diagnosis, to receive regular hospital diet, therapeutic diet and medical nutrition therapy administrated by a team of experts, and the government has the duty to guarantee it. Conclusion The right to nutritional care can be considered as a human right by itself. Violating the right to nutritional care may often impair the enjoyment of other human rights, such as the rights to health or food and vice versa. The main impact of this recognition is attended to be at the national and international policies level. Knowing that the relation between human rights and nutritional care is a new issue, more research is warranted to ascertain its precise nature.